2022
DOI: 10.1002/sd.2309
|View full text |Cite
|
Sign up to set email alerts
|

For sustainable development in the transportation sector: Determinants of acceptance of sustainable transportation using the innovation diffusion theory and technology acceptance model

Abstract: With global interest in environmental concerns, the importance of sustainable development has consistently increased. With this trend, the concept of sustainable transportation is an urgent issue in both developed and developing countries. Thus, the current study examines user adoption of sustainable transportation and proposes an integrated model of two theoretical frameworks: the innovation diffusion theory and technology acceptance model. The structural results with 250 respondents in Korea find a sequentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…This suggests that the more benefits from the used technology observed, the more likely this technology is to be adopted. However, studies like Ahn & Park (2022) and Qazi et al, (2018) found no association between observability and attitude. The current study seeks to prove the following: H6: Observability is positively associated with perceived attitude.…”
Section: Observabilitymentioning
confidence: 91%
“…This suggests that the more benefits from the used technology observed, the more likely this technology is to be adopted. However, studies like Ahn & Park (2022) and Qazi et al, (2018) found no association between observability and attitude. The current study seeks to prove the following: H6: Observability is positively associated with perceived attitude.…”
Section: Observabilitymentioning
confidence: 91%
“…That line of work has flourished (e.g. Ahn & Park, 2022; Chindasombatcharoen et al, 2021; Koseoglu et al, 2022; Sehnem et al, 2022; Sinha, 2021). In this respect, Steffen et al remark: “The PB (planetary boundaries) framework does not dictate how societies should develop.…”
Section: Alternatives Eroded By the Growth Paradigmmentioning
confidence: 99%
“…This gives rise to SDG11, which refers to the transition to more inclusive, safe, resilient, and sustainable cities. SDG11 has come to guide the management of cities around the world in recent years; consequently, nations are actively trying to rebuild their political policies to improve the sustainability of society [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Min et al [ 10 ] indicate that in the field of the sharing economy as a whole, most recent studies have focused on the business or government perspective, its impact on the tourism sector, regulation, or its impact on overall sustainability, rather than focusing on the consumer perspective. Specifically, in the field of mobility, Ahn and Park [ 2 ] and Wang et al [ 11 ] state that few studies so far have focused on citizens’ perceptions of sustainable transport systems, which are widespread in both developed and developing countries, and therefore advocate the need to carefully consider the user’s perspective in the development of mobility initiatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation